2020
DOI: 10.1159/000510241
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clinical Cases of Malignant PEComa via Comprehensive Genomic Profiling of DNA and RNA

Abstract: <b><i>Purpose:</i></b> Perivascular epithelioid cell tumor (PEComa) is a rare mesenchymal soft tissue neoplasm often linked to mTOR pathway activation via TSC2 mutation. We analyzed a series of 31 consecutive metastatic PEComa (mPEComa) cases using a combined DNA/RNA hybrid capture-based comprehensive genomic profiling (CGP) assay to assess the genomic landscape of mPEComa. <b><i>Patients and Methods:</i></b> Formalin-fixed, paraffin-embedded (FFPE) blocks or sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…Among them, 88 reports fulfilling the inclusion criteria were included in this review (Figure 1). The retained reports were mostly case reports (n = 71) , followed by retrospective case series (n = 16) [15,17,[91][92][93][94][95][96][97][98][99][100][101][102][103][104] and only one of them was a report of a prospective The retained reports were mostly case reports (n = 71) , followed by retrospective case series (n = 16) [15,17,[91][92][93][94][95][96][97][98][99][100][101][102][103][104] and only one of them was a report of a prospective phase II trial [18]. Details on all the 124 cases reports, case by case are available in Table S1 (Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 88 reports fulfilling the inclusion criteria were included in this review (Figure 1). The retained reports were mostly case reports (n = 71) , followed by retrospective case series (n = 16) [15,17,[91][92][93][94][95][96][97][98][99][100][101][102][103][104] and only one of them was a report of a prospective The retained reports were mostly case reports (n = 71) , followed by retrospective case series (n = 16) [15,17,[91][92][93][94][95][96][97][98][99][100][101][102][103][104] and only one of them was a report of a prospective phase II trial [18]. Details on all the 124 cases reports, case by case are available in Table S1 (Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…Less than 30% of articles were published in 2012 or before (n = 26), whereas more than 40% were published in the last five years (n = 36) (Figure 2). Seven cohorts were included in this review, all with different results reported given the variability of collected data between articles [17,18,97,98,101,102,104] (Table 1). The number of patients included in these studies varied between 7 to 50, patients were mostly female with a median age between 47.5 to 67 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Three TFE3 ‐rearranged PEComas also underwent targeted exome sequencing, but none harbored TSC2 or TP53 mutations, highlighting how TFE3 fusions and TSC2 mutations are mutually exclusive. Similarly, in a recent series of 31 malignant PEComas subjected to DNA and RNA profiling, 5 (16%) tumors harbored a TFE3 fusion, but were wildtype for TSC1 , TSC2 , and FLCN 79 . Other fusion partners that have been detected include NONO , 79,85‐87 RBMX , 88 PRCC , 79,89 RBM10 , 79 and ZC3H4 , 79 but overall SFPQ/PSF appears to be the most recurring gene associated with TFE3 ‐rearranged PEComas 90 …”
Section: Molecular Featuresmentioning
confidence: 92%
“…A recent study evaluating DNA and RNA genomic profiles in 31 malignant PEComas (one uterine, one ovarian) detected TSC2 alterations in 10 (32%), TSC1 mutations in 3 (10%), and FLCN (folliculin, another protein in the mTOR pathway) in 2 (6.5%) 79 . Biallelic inactivation was noted in most (7/10; 70%) TSC2 ‐alterated PEComas and in all TSC1‐ and FLCN ‐mutant tumors.…”
Section: Molecular Featuresmentioning
confidence: 99%
“…In a recent issue of Oncology , Akumalla et al [7] performed an in-depth analysis of the genomic landscape of malignant PEComas using NGS. The analysis sheds further light not only on the pathogenesis of mPEComas but helps explain the response to mTOR inhibitors as well.…”
mentioning
confidence: 99%